SYNONYMS AND PARA-SYNONYMS IN CAPITALS OF NORTHEASTERN OF BRAZILIAN: ALiB DATA - DE ARAGÃO, Maria do Socorro Silva (2015)
Scholars of semantics, since time immemorial, have given particular attention to the problem of synonymy and from these studies, several questions are raised about whether or not synonymous. If they exist, they are defined, how they work, what is your status in cognitive and / or affective terms, if they are absolute or partial, it is limited to the denotation or connotation attached to each particular context.